PENGARUH UMUR PERUSAHAAN, OPINI AUDIT, REPUTASI KAP, DAN KOMPLEKSITAS OPERASI TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-2019 - Fajar Laksono Dimas; Akbar Nasrizal; Putra Agri Adhitya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to examine the effect of Company Age, Audit Opinion, KAP Reputation, and operation complexity on timeliness of financial reporting. The populations in this study are 42 mining companies listed in the Indonesia Stock Exchange (IDX) during the period 2017-2019. The research method used in this study is a quantitative method which aims to test the relationships between variables through testing hypotheses by using 108 observation in 36 companies for three periods. The sample selection method uses purposive sampling in mining companies listed in the Indonesia Stock Exchange during the 2017-2019 periods. Hypothesis testing techniques are carried out using logistics analysis using the SPSS program. The results of this research show that company age, audit opinion, kap reputation, and operation complexity have an effect on timeliness of financial reporting.Keyword : Company Age, Audit Opinion, Kap Reputation, Operation Complexity, And Timeliness Of Financial Reporting.